Cadherin interaction probed by atomic force microscopy - Baumgartner, W. (The National Academy of Sciences, 2000)
Single molecule atomic force microscopy was used to characterize structure, binding strength (unbinding force), and binding kinetics of a classical cadherin, vascular endothelial (VE)-cadherin, secreted by transfected Chinese hamster ovary cells as cis-dimerized full-length external domain fused to Fc-portion of human IgG. In physiological buffer, the external domain of VE-cadherin dimers is a ≈20-nm-long rod-shaped molecule that collapses and dissociates into monomers (V-shaped structures) in the absence of Ca(2+). Trans-interaction of dimers is a low-affinity reaction (K(D) = 10(−3)–10(−5) M, k(off) = 1.8 s(−1), k(on) = 10(3)–10(5) M(−1)·s(−1)) with relatively low unbinding force (35–55 pN at retrace velocities of 200–4,000 nm·s(−1)). Higher order unbinding forces, that increase with interaction time, indicate association of cadherins into complexes with cumulative binding strength. These observations favor a model by which the inherently weak unit binding strength and affinity of cadherin trans-interaction requires clustering and cytoskeletal immobilization for amplification. Binding is regulated by low-affinity Ca(2+) binding sites (K(D) = 1.15 mM) with high cooperativity (Hill coefficient of 5.04). Local changes of free extracellular Ca(2+) in the narrow intercellular space may be of physiological importance to facilitate rapid remodeling of intercellular adhesion and communication.